Hak Prerogatif Presiden Menerbitkan Peraturan Pemerintah Pengganti UndangUndang Dengan Dasar Kegentingan Memaksa - Panggabean, Pilipi; Lestari, Maria Maya; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
One of the prerogatives of the President of the Republic of Indonesia is to issue a Government Regulation in Lieu of Law (Perppu). Article 22 of the 1945 Constitution explains that "In the case of a compelling urgency, the President has the right to stipulate government regulations in lieu of laws. The historical dynamics of laws and regulations in Indonesia show that the background for the issuance of Perppu by the president is generally different. This is due to the fact that the benchmark "Forcing urgency" is always multi-interpretable and the president's subjectivity is large in interpreting the "Forcing urgency" as the basis for the issuance of Perppu, in fact, there is often a proverb in the community that perppu is generally formed not because of a compelling urgency, but because of a President personal interest..This type of research can be classified as normative research with a statutory and historical approach. The data collection technique in this research is literature study, after the data is collected then analyzed to draw conclusions.The results of this study are: First, the prerogative of the President of the President to issue is obtained from the authority of the Delegative President which comes from the legislative authority. The Perppu which was formed on the basis of the urgency of forcing it should not limit Human Rights (HAM) and the president's interpretation in issuing the Perppu is no longer subjective but has been regulated by the Constitutional Court Decision No. 138/PUU-VII/2009. Second, the Perppu issued in 2015 – 2020 has fulfilled the element of coercion based on the Constitutional Court Decision Number 138/PUU/VII/2009.Keywords: President's Prerogative, Perppu, Forced Urgency.